The communication style of Habib Jafar's da'wah on TikTok social media - Naqisa, Zikrina Istighfara; Fadillah, Dani (Universitas Negeri Yogyakarta, 2024)
This research aims to explore in depth the communication style of Habib Ja'far's preaching on the social media TikTok. Husein Hadar Jafar or more commonly known as Habib Jafar, who is a young preacher, uses the TikTok platform as a means of preaching which is attractive to many young millennials and Gen Z. This researcher used a descriptive qualitative approach, with an audio-visual method of analyzing the content of R. Hosetly's TikTok account @husein jafar. Other sources were obtained using various references in the form of scientific journals, books, and media coverage. The conclusion obtained from this research is that the preaching communication style on TikTok social media uses inductive qualitative. Habib Jafar preaching through the TikTok platform invites the younger generation to re-acquaint themselves with Islam with an assertive communication style.